Recent advances in organic light-emitting diodes: toward smart lighting and displays - Zou, Shi-Jie; Shen, Yang; Xie, Feng-Ming; Chen, Jing-De; Li, Yan-Qing; Tang, Jian-Xin (Materials chemistry frontiers, 2020)
Organic light-emitting diodes (OLEDs) have rapidly grown as one of the leading technologies for full-color display panels and eco-friendly lighting sources due to their outstanding features including superior color quality, wide viewing angle, mercury-free manufacture, fascinating flexibility, etc. A variety of materials, device architectures, as well as processing techniques have been investigated for optimizing device performance in order to fulfill the requirements of lighting and display applications. In this review, we first summarize the light emission mechanisms of electroluminescent materials. Then, the designed device architectures aiming at the realization of various light emission mechanisms are reviewed. An overview of recent advances in light extraction strategies is presented since all efficient OLEDs have a multi-thin-film structure, which leads to severe light trapping in devices. In addition, the progress of flexible OLEDs is reviewed from the aspect of flexible transparent electrodes because of their great potential in flexible displays. Most recent breakthroughs of solid-state lighting and displays are briefly addressed as well. A brief perspective on future research is also proposed for pursuing the commercialization of OLEDs. Recent advances in organic light-emitting diodes toward smart lighting and displays are reviewed in terms of materials, devices, fabrication and applications.